NUPES : protagonista da política para educação superior brasileira? (1989-2005) - Grello, Fabíola Bouth (2008)
The aim of this work is to analyze the NUPES academic production, specifically 23 serial researches of Work Documents periodic from 1989 to 2005. The principal objective is to investigate if NUPES academic production was antecipated, in scientific means, to political process and educational laws development process since 90´s decade, keeping in mind Brazilian superior educational official changes. Our specific aim is to identify the concept of scientific publication autonomie of this section, and this concept evolution also. We tried to reflect how political aspirations, vizualazed and projected by NUPES for almost two decades are been incorporeted by educational law arcabouço and based on science and tecnologie Conselho Nacional de Desenvolvimento Científico e Tecnológico-CNPq, analized here by the editais from 2003-2004. The research point out evidences that NUPES proposal Project after 16 years turned them not only a protagonist but na important part of thematic, theorical and methodological field of superior educational reform process. Their researchs, publications, discussions abreviated politics that are incorporate to life by laws, decrees, and measures. The politics point out that the State is suffering a new political orientation, that had been done by NUPES from two decades in BRazil. These orientations focusing on public universities has been materializing under political forms stimulating the management switc, employes hire, its spend, and the new function that demands to the university. All the analysis bring us to a commun place, indicating a academic culture, professor-researcher profile (now a entrepreneur) and flexibility that this politics demands, are changing movements into the university, indicating less scientific autonomie power in academic university space. All this movement bring us to a new State politics, that uses public means to invest in politics direct from productiv section, providing a new knowedlege dimension, not meeting politic and academic time neither social comportament, breaching the three pilars of the university: scientific, financial and didactic autonomy.